PENGARUH SUPPLY CHAIN MANAGEMENT, TOTAL QUALITY MANAGEMENT, MARKETING CAPABILITY TERHADAP COMPETITIVE ADVANTAGE KECAP MAJALENGKA - Ramadhan , Farhan Kusuma; Alhazami, Lutfi (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2023)
Intense competition requires companies to continue to maintain their maximum level of production. that is, it basically develops from the value that the organization is able to create to its buyers. This study aims to determine the effect of supply chain management, total quality management, and marketing capability on competitive advantage in the Majalengka Triangle soy sauce company as one of the companies that produce soy sauce since 1958. This study was conducted with a quantitative approach and associative research design with a sample of 51 respondents. The instrument used by researchers is a questionnaire. Quality testing on research instruments is a test of validity and reliability. Data analysis uses descriptive analysis, while for hypothesis testing using multiple linear regression analysis with the help of Statistical Package for Social Sciences (SPSS) 25. The results of this study explain that there is a positive and significant relationship between supply chain management, total quality management, marketing capability to competitive advantage with a correlation coefficient value below 0.05. This analysis is conducted on one company and does not take into account other variables or moderator variables that affect supply chain management.